2007
DOI: 10.1021/pr0702161
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Changes Induced by Knock-Down of the Deubiquitylating Enzyme HAUSP/USP7

Abstract: Modification of proteins by ubiquitin plays a major role in a broad array of biological processes. Reversal of this process through deubiquitylation likely represents an important regulatory step in the maintenance of cellular homeostasis. However, the biological functions of deubiquitylating enzymes still remain poorly characterized. To investigate the biological role of the herpes virus-associated ubiquitin-specific protease HAUSP/USP7, we have generated stably transfected cells carrying inducible shRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…HAUSP, on the contrary, probably has a selective set of substrates (64). Indeed its removal using RNA interferencebased strategies does not lead to global changes in ubiquitination (64) even if it has major implications on cellular growth through action on the p53 pathway (65).…”
Section: The Affinity Purification Procedures Described Is Efficient Fmentioning
confidence: 99%
“…HAUSP, on the contrary, probably has a selective set of substrates (64). Indeed its removal using RNA interferencebased strategies does not lead to global changes in ubiquitination (64) even if it has major implications on cellular growth through action on the p53 pathway (65).…”
Section: The Affinity Purification Procedures Described Is Efficient Fmentioning
confidence: 99%
“…USP7 (HAUSP) functions as a deubiquitylase that regulates the stability of both p53 and MDM2 (9,10) as well as a number of other proteins (11)(12)(13). We found that USP7 physically interacts with UHRF1.…”
mentioning
confidence: 92%
“…A number of USP7 substrates have been identified, and USP7 knockdown was shown to affect cellular levels of at least 36 proteins in LS174T colon carcinoma cells (4). Among a variety of substrates, the USP7 deubiquitinates both p53 tumor suppressor and its main regulator E3 ligase Hdm2 (human double minute 2) and thus plays a central role in maintaining an appropriate p53 level in the cell (5)(6)(7)(8).…”
mentioning
confidence: 99%